(untitled) (Impetus, 2025)
This article presents the progress of a research study aimed at understanding how institutional and leisure-related discourses and practices enhance or inhibit positive mental health among adolescents in an educational institution in Medellín, Colombia. The methodological perspective is based on collaborative research and the ethnographic-reflexive method, which seeks to give voice to the educational community. This approach moves away from investigating “about” the reality of the actors and instead engages “with” them in continuous interaction. The concept of positive mental health is addressed from a broad and complex perspective, recognizing social, cultural, environmental, and political factors that determine emotional and psychological well-being. Additionally, a critical stance on leisure is proposed, based on the notion of abigarrado leisure, which acknowledges the diversity of recreational, popular, and traditional activities that emerge as forms of resistance against a leisure industry centered on consumption. Popular education in formal educational settings is understood as a means to construct essential knowledge for communities. Among the findings, academic pressure, lack of freedom in school, and the absence of leisure activities are identified as factors that inhibit positive mental health among adolescents, who, in response, develop strategies to disconnect from their reality. Furthermore, the influence of the family environment and the use of technology also play a crucial role in their emotional and physical well-being.